PP.29 The Personal and Professional Impact of Stillbirth on Consultant Obstetricians. (26th April 2013) - Nuzum, D; Meaney, S; O'Donoghue, K
Abstract : Objective: Stillbirth remains amongst the most challenging areas in obstetric practise. In Ireland, consultant obstetricians are ultimately responsible for care provided to mothers following stillbirth. This study explores the impact of stillbirth on consultants working in an Irish tertiary maternity hospital (9, 000 births per annum) where the stillbirth rate is 4.6/1000. Study design: Semi-structured qualitative interviews lasting 30–60 minutes were conducted in 2012 with a sample of 8 consultant obstetricians and gynaecologists. The study explored how consultants care for parents following stillbirth and the impact of stillbirth on them personally and professionally. The data were analysed using Interpretative Phenomenological Analysis. Results: Stillbirth was identified as one of the most difficult experiences for most consultants. Most consultants described it as amongst 'the most devastating news'. Two felt stillbirth was not the worst outcome. The human response and the weight of responsibility were the dominant personal and professional themes. All felt that bereaved parents should receive direct care from a consultant. The possibility of a medico-legal challenge was a significant factor-mostly for those who are primarily gynaecologists resulting in the question "what have I missed?". The personal impact of stillbirth is considerable: most participants were emotional during interview. Conclusion: Despite the impact and importance of stillbirth care, none of the obstetricians received any formal training in perinatal bereavement care. This study highlights a gap in training and the impact of stillbirth on obstetricians professionally and personally. Medico-legal concerns following stillbirth potentially impact on the depth of care and warrants further research.